General overview of the potential effect of extreme temperature change on society and economyin Poland in the 21st century - Jędruszkiewicz, Joanna (Array, 2020)
This work gives an overview on how the projected changes in the extremes in Poland might impact human health and economy. For that purpose, statisti-cally corrected data from 7 regional climate models were used. A significant increase of extreme hot events (i.e. heat waves, tropical nights) is projected for Central and Southern Poland for the end of the 21st century which might seri-ously affect a society living in large urban areas. Less extreme cold events im-prove thermal comfort in winter. The negative impact of the warming will affect energy systems with higher demand for electricity in summer and agriculture: an earlier beginning of the growing season and flower blooming will enhance the risk of frost damages in spring, whereas excessive heat will reduce yields in summer. Polish tourism should benefit from higher thermal comfort (except for hot July and August in the far future and warming in the winter season bring-ing snow cover depletion in the near future).